HUBUNGAN PEMBERIAN PENGUATAN PEMBELAJARAN MELALUI DARING DENGAN MOTIVASI BELAJAR PADA MASA PANDEMI COVID-19 - Andrianus Nababan; Dame Taruli (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2021)
This study aims to determine the relationship and the magnitude of the provision of strengthening learning through online by PAK lecturers with learning motivation among undergraduete students in IAKN Tarutung. This research was conducted by using inferential quantitative research. The population of this study was the forth semester of IAKN Tarutung. The total number of the students was 196 students. In order to determine the sample, the stratified random sampling was used to select that were 49 students as participants involved. The research instrument was a closed questionnaire with a total of 40 items. The data of the study were analyzed by using descriptive and inferential statistical data analysis techniques with the following steps: (1) The relationship test found that rcount> rtabel is 0.673> 0.266. It showed that there is a positive relationship between reinforcement with the learning motivation of IAKN Tarutung students, (2) The significant test of the relationship shows that tcount> ttable is 6.691> 2,000. It showed that there is a significant relationship between giving reinforcement of online learning and learning motivation. Therefore, it can be concluded that the strengthening of online learning in the Covid-19 pandemic situation is the ability of lecturers to innovate in designing and concocting materials, learning methods, and what applications are in accordance with the material and methods so that lecturers become creative and can motivate students to stay enthusiastic in learning online (online) and not be a psychological burden. Keywords: Lecturer Strengthening, Online Learning, Learning Motivation, Covid-19 Pandemic